Systematic Literature Review (Slr) Based On Prisms And Analysis Bibliometrics: Influence Price And Service Value On Customer Loyalty Mediated By Customer Trust And Satisfaction At The Galeong Barbershop Faceoff - William Janaldo; Eko Budi Soetjipto; Madziatul Churiyah (JURNAL ECONOMINA, 2026)
This study aims to analyze the development of studies on the influence of price and service value on customer loyalty. trust And satisfaction customer as variables mediation. The study used a PRISMA-based Systematic Literature Review (SLR) approach combined with bibliometric analysis to map publication trends, keyword structure, theme density, and research collaborations. Data were obtained from the Scopus database for the 2020-2026 period, focusing on the keywords price, service value, customer trust, customer satisfaction, and customer loyalty. The selection results showed that 4,643 articles met the inclusion criteria for further analysis. Bibliometric findings show that customer loyalty is a central node. Which related close with price, service value, customer trust, customer satisfaction, repurchase intention, and word of mouth. Substantively, fair pricing and high service value contribute to customer loyalty, both directly and through increased trust and satisfaction. This study provides theoretical contributions to the services marketing literature and implications. practical for manager barbershop in designing pricing strategy, service experience, and ongoing customer relationships.